Strengthening the capacity of civil servants in policy formulation and implementation for innovation in Vietnam - Do Thi Vui (Journal of State Management, 2025)
In the context of the Industrial Revolution 4.0 unfolding at an unprecedented pace, innovationhas increasingly become essential for governments worldwide to respond to rapidly evolving andcomplex socio-economic challenges effectively. Within this process, cadres and civil servantsplay a pivotal role in formulating and implementing policies that promote innovation in both thepublic sector and broader society. This paper examines the role of cadres and civil servants in thedevelopment and implementation of innovation policies in Vietnam. It also assesses the currentsituation and proposes several solutions to enhance this workforce's capacity, therebycontributing to sustainable development in the era of digital transformation and internationalintegration.